Primary and secondary anti-viral response captured by the dynamics and phenotype of individual T cell clones - Minervina, Anastasia A; Pogorelyy, Mikhail V; Komech, Ekaterina A; Karnaukhov, Vadim K; Bacher, Petra; Rosati, Elisa; Franke, Andre; Chudakov, Dmitriy M; Mamedov, Ilgar Z; Lebedev, Yuri B; Mora, Thierry; Walczak, Aleksandra M (eLife, 2020)
The diverse repertoire of T-cell receptors (TCR) plays a key role in the adaptive immune response to infections. Using TCR alpha and beta repertoire sequencing for T-cell subsets, as well as single-cell RNAseq and TCRseq, we track the concentrations and phenotypes of individual T-cell clones in response to primary and secondary yellow fever immunization — the model for acute infection in humans — showing their large diversity. We confirm the secondary response is an order of magnitude weaker, albeit ∼10 days faster than the primary one. Estimating the fraction of the T-cell response directed against the single immunodominant epitope, we identify the sequence features of TCRs that define the high precursor frequency of the two major TCR motifs specific for this particular epitope. We also show the consistency of clonal expansion dynamics between bulk alpha and beta repertoires, using a new methodology to reconstruct alpha-beta pairings from clonal trajectories.